2014
DOI: 10.1111/boj.12202
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and ecological niche modelling of the restrictedRecordia reitzii(Verbenaceae) from southern Brazilian Atlantic forest

Abstract: Genetic diversity analyses, coupled with ecological niche modelling (ENM) of species with a restricted distribution, may provide valuable information for understanding diversification patterns in endangered areas. We analyzed the genetic diversity of Recordia reitzii, a tree restricted to the threatened and highly fragmented Brazilian Atlantic forest, using three intergenic cpDNA spacers and ten microsatellite (SSR) loci. To assess the historical processes that may have influenced the distribution of extant R.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 105 publications
(149 reference statements)
4
13
0
Order By: Relevance
“…The most suitable areas during the LGM occurred in the south and southeast of Brazil, mainly from 23°S to 27°S from the Santa Catarina to São Paulo states (Fig. D), making evident that the appropriate ranges for V. incurvata occupation in the continental shelf during the LGM are now submersed, as similarly observed in other studies (Pinheiro et al., ; Thode et al., ; Leite et al., ; Segatto et al., ). Our V. incurvata results for MH showed that the suitable areas are very similar to those observed in the present (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…The most suitable areas during the LGM occurred in the south and southeast of Brazil, mainly from 23°S to 27°S from the Santa Catarina to São Paulo states (Fig. D), making evident that the appropriate ranges for V. incurvata occupation in the continental shelf during the LGM are now submersed, as similarly observed in other studies (Pinheiro et al., ; Thode et al., ; Leite et al., ; Segatto et al., ). Our V. incurvata results for MH showed that the suitable areas are very similar to those observed in the present (Fig.…”
Section: Discussionsupporting
confidence: 83%
“…Overall, our results suggest that P. actinia has an ancient evolutionary history in the Atlantic Forest and could have been subjected to forces that induced the species to retract and expand its geographical distribution. This situation also probably occurred in another species, Recordia reitzii (Moldenke) Thode & O'Leary (Verbenaceae), an endemic shrub that has similar levels of genetic diversity and a similar distribution (Thode et al ., ). As in R. reitzii , forest fragmentation and Pleistocene sea‐level changes could have affected the genetic diversity and species distribution in P. actinia .…”
Section: Discussionsupporting
confidence: 92%
“…Population genetic analyses and phylogeographical studies have been conducted in the Atlantic Forest to explain the origin of plant species diversity (for a review, see Turchetto‐Zolet et al ., ), but a general explanation is far from being established, especially as it seems that different forces have acted in the north (Ribeiro et al ., ) and south (Thode et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, molecular phylogeographic approaches facilitate an increased understanding of the role that historical events play in the geographical patterns of genetic variability within and among species (Knowles & Maddison, ; Avise, ). Studies combining ecological and phylogenetic/phylogeographic analysis have provided information regarding the origin and evolutionary history of species (Wiens & Donoghue, ; Ricklefs, ) and improved our understanding of the processes structuring genetic variation across landscapes (Knowles, ; Chan, Brown & Yoder, ; Collevatti et al ., ; Alvarado‐Serrano & Knowles, ; Diniz‐filho et al ., ; Thode et al ., ).…”
Section: Introductionmentioning
confidence: 97%